COMPARATIVE STUDY OF THE MOTOR PROFILE OF INFANT SIBLINGS OF CHILDREN WITH AND WITHOUT AUTISM (Fiep Bulletin - online, 2014)
The present study has as goal to compare the motor profile of infant siblings of children with and without autism about the developmental perspective. It characterizes as a descriptive research. The sampling has been constituted with 10 both sex children. For the study, groups A and B have been constituted with infant siblings with and without autism of same chronological age enrolled in the regular public school in the city of Maceió in Alagoas. Besides, individuals' infant siblings of study are also the same chronological age in the period of realization of tests.  Instruments that have been used were:  semi-structured interview and Rosa Neto's Scale of Motor Development – SMD (2002). Results demonstrated that: group A presents a negative age in relation to the General Motor Age (GMA). On the group B were found positive age in relation of the same aspect. The categories of motor development, fine motility and spatial organization of six tested categories were the unique ones that presented positive motor age in the group A.  On the group B all of six evaluated categories present positive motor age. Results of the general motor quotient demonstrated classification of group A on normal average, while the group B presented raising normal classification with meaning differences among the groups. It concludes that people's infant siblings without autism present better results in relation to the motor abilities, when it is compared to people's infant siblings with disorders. In this sense, it suggests that these ones are included in public policies directed to attention of people with autism, profiting lesser deficits of disorders to the familiar nucleus.
Keywords: Motor Evaluation; Autism; Infant Siblings.